Kata Adalah Senjata: Sastra dan Perlawanan Zapatista dalam Menghadapi Pemerintah Meksiko - Nugraha, Dediyan Adnan (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2023)
ABSTRACT This research aims to conduct an in-depth study of Zapatista literature and resistance in dealing with the neoliberal Mexican government. In general, this research wants to answer the question of